2016
DOI: 10.1038/srep39400
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2, Angiopoietin-1 and subclinical cardiovascular disease in Chronic Kidney Disease

Abstract: Angiopoietins (Angpt) and vascular endothelial growth factor (VEGF) have been associated with cardiovascular disease. The study enrolled 270 pre-dialysis stage 3–5 CKD patients to assess the link between circulating Angpt2, Angpt1 and VEGF-A and subclinical measures of cardiovascular structure and function. Serum markers of angiogenesis were measured using commercial enzyme-linked immunosorbent assays. Cardiac structure and function were examined by echocardiography. Brachial-ankle pulse wave velocity (baPWV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 28 publications
5
20
0
Order By: Relevance
“…In addition, serum Angpt2 levels has been correlated with subclinical cardiovascular diseases such as fractional shortening, number of carotid plaques [21] and carotid intima media thickness [22]. In our previous reports, we found that CKD patients with high serum Angpt2 levels were more likely to have high brachial-ankle pulse wave velocity, high left ventricular mass index and left ventricular hypertrophy [23]. Serum Angpt2 was associated with abnormal cardiovascular structure, and increased cardiovascular burden.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, serum Angpt2 levels has been correlated with subclinical cardiovascular diseases such as fractional shortening, number of carotid plaques [21] and carotid intima media thickness [22]. In our previous reports, we found that CKD patients with high serum Angpt2 levels were more likely to have high brachial-ankle pulse wave velocity, high left ventricular mass index and left ventricular hypertrophy [23]. Serum Angpt2 was associated with abnormal cardiovascular structure, and increased cardiovascular burden.…”
Section: Discussionmentioning
confidence: 98%
“…Our study sample was found to have a similar growth factor milieu, with angiopoietin-1 deficiency relative to excess VEGF-A among CKD patients. A recent study suggested that low angiopoietin-1 level was positively associated with abnormal cardiac structure in stages 3–5 CKD patients [ 42 ]. Further studies are warranted to investigate whether imbalanced angiopoietin-1 and VEGF-A may be associated with an increased risk of ESRD and CVD in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated angiopoietin-2, a natural antagonist of angiopoietin-1, which leads to aberrant neovascularization and endothelial abnormalities [32]. Moreover, angiopoietin-2 has been recently identified as a prognostic biomarker of cardiovascular events and mortality in chronic kidney disease patients [33] and those with subclinical cardiovascular disease [34]. Together with the syndecan-1 findings, the reduced levels of angiopoietin-2 in patients submitted to training permit us to speculate that RMT has a great potential to have a positive impact on cardiovascular disease, a highly prevalent condition in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%